PERAN ABSEN ELEKTRONIK DALAM MENINGKATKAN DISIPLIN PEGAWAI PADA MASA PANDEMI DI KANTOR KECAMATAN BANYUMAS KABUPATEN PRINGSEWU - Anton Dwi Wahyono; Refli Setiawan (e-JKPP, 2021)
The problems in this study are: (1) How is the Role of Electronic Absence in Improving Employee Discipline During the Pandemic Period at the Banyumas District Office, Pringsewu Regency. (2) What are the aspects that hinder the role of electronic absences in improving employee discipline during the pandemic period at the Banyumas District Office, Pringsewu Regency.This research method is using qualitative descriptive research. The use of this method is to describe the role of electronic absences in improving employee discipline during the pandemic at the Banyumas District Office, Pringsewu Regency, to examine qualitatively, how all data were obtained directly from informants in the field using interviews and document studies.The results showed that the Role of Electronic Absences in Improving Employee Discipline During the Pandemic In the Banyumas District Office, Pringsewu Regency, had been implemented, the Head of the Religious Affairs Office had implemented existing regulations by implementing electronic absences, although the implementation was not optimal, this was because there was no application of sanctions. clearly against employees who violate the provisions on employee discipline.The inhibiting aspects, namely, (1) The Role of Electronic Absence in Improving Employee Discipline During the Pandemic Period at the Banyumas District Office, Pringsewu Regency, has not been fully implemented in a timely manner by employees. (2) There are still certain employees who often work not according to a predetermined schedule, and often work not the main tasks that should be carried out, so that these employees do not carry out their work optimally. (3) Often does not become a reference in assessing employees about discipline, and is more inclined to the closeness of the leadership and employees concerned in measuring employee discipline.